Meningkatkan Hasil Belajar PAK Pada Materi Manusia Makhluk Otonom Melalui PBL Berbantuan E-LKPD Kelas X SMAN 1 Palangkaraya - Ernita Fransiska (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
. Education problems in Indonesia cover various aspects that influence the quality and effectiveness of learning. Some of these problems include irrelevant curricula, variations in the quality of teacher teaching, shortage of qualified teachers, inadequate educational facilities, less interactive learning methods, emphasis on standardized tests, limited technology in learning, unequal online access, and inadequate parental involvement. limited. Improvement efforts have been made through curriculum development, teacher training, facility improvements, use of interactive learning methods, holistic assessment, technology integration, and overcoming inequalities in access. The government has innovated by introducing the Independent Curriculum as an educational approach that is more contextual, interactive and student-centered. However, research shows that student learning outcomes in the material